Advances in pathogenesis and treatment of ocular involvement in Behcet’s disease - Lin, Suibin; Xu, Zhirong; Lin, Zhiming; Xie, Baozhao; Feng, Junmei (Frontiers in Immunology, 2023)
Behcet's disease (BD) is a chronic multi-systemic disease characterized by relapsing-remitting oral ulcers, genital ulcers, ocular inflammatory involvements, and numerous other systemic features. Ocular involvements are quite common in BD and may cause severe tissue damage and potentially blindness. Even though the pathogenesis of BD remains ambiguous, growing evidences have shown that genetic factors, environmental triggers and immunological abnormalities play significant roles in its development and progression. Novel biotherapies targeting IFN-γ, TNF-α and interleukins have been used in recent years. In this review, we mainly pay attention to the ocular involvement of BD, and discuss the current understanding of mechanisms and advances in therapeutic approaches, especially novel biologics. Finally, we discuss the management in patients with pregnancy.